(untitled) (diségno, 2018)
The monumental editorial initiative to publish a National Edition of De prospectiva pingendi by Piero della Francesca (Sansepolcro c. 1410-1492) has recently been completed. The initiative is sponsored by the Ministry of Cultural Heritage and Activities and Tourism (MiBACT) and the Fondazione Piero della Francesca [1]. The book, published by the State Mint and Polygraphic Institute, is the third volume in the epic series –the National Edition of Writings by Piero della Francesca– established by Presidential Decree 26.2.1974 and initiated in 1985 (read more).